MANAGEMENT OF DEVELOPMENT AND IMPLEMENTATION HIDDEN CURRICULUM TO INCREASE STUDENT CREATIVITY IN HIGHER EDUCATION - Juanda, Anda; Ansori, Yoyo Zakaria (Ridwan Institute, 2024)
The purpose of this study is to study, describe, and develop and even find new theories of management, development and implementation of hidden curriculum, social aspects, increase student creativity. The study's originality lies in the integration of these variables, offering fresh perspectives and practical implications for educators and policymakers in fostering student creativity through curriculum development. The research method used in this study was mixed methods, conducted at UNSWAGATI, UMC, UNTAG, and IAIN Syekh Nurjati Cirebon. The sampling method was purposive sampling, based on financial resources, study duration, and expected outcomes. The results of the study show that the implementation of the hidden curriculum management has a significant influence on the internalization of values and the formation of student character. The development management and hidden curriculum play an important role in enhancing student creativity by creating an environment that supports innovation and encourages exploration. It would be valuable to investigate how different types of educational environments, programs, and leadership styles impact the development of 21st-century skills, particularly creativity, in both academic and professional settings, providing insights into best practices for cultivating innovative and adaptable future leaders.